Moretti goes Didactics. Quantitative Empirie, Schwellisierungen und literaturdidatische Digital Humanities (Fokus Distant / Scalable Reading) - Herz, Cornelius (MiDU – Medien im Deutschunterricht, 2024)
Die Verbindungslinien zwischen Digital Humanities (DH) und Literaturdidaktik sind in Anbetracht des geringen Umfangs bisheriger Ansätze nicht unmittelbar evident. Deswegen thematisiert der erste Teil des vorliegenden Beitrags Berührungspunkte für eine weiterführende literatur- und mediendidaktische Auseinandersetzung. Der zweite Teil skizziert ergänzend Parallelen in der Entwicklung von wissenschaftlicher Methodik im Spiegel der Mediengeschichte und fragt, wie man die eigene Forschungsgeschichte erzählt, wozu der Begriff der ‚Schwellisierung‘ vorgeschlagen wird. Auf diesen Grundlagen wird eine Arbeitsdefinition für literaturdidaktische DH erstellt. Der dritte Teil führt schließlich konkrete Beispiele für DH in der Literaturdidaktik mit einem Schwerpunkt auf der rechnergestützten, quantitativen Analyse von Curricula aus (Distant bzw. Scalable Reading). Abstract (english): Moretti goes Didactics. Quantitative Empirical Research, Thresholdisation and Digital Humanities in Literature Didactics (Focus On Distant / Scalable Reading) Connections between digital humanities (DH) and literature didactics appear to be rather scarce so far, at least with regard to the number of existing attempts. Hence, the first part of the paper at hand addresses potential overlaps for an advanced approach in literature and media didactics. The second part outlines further parallels considering the development of scientific methods as reflected in media history and asking how to tell one’s own history of research. In this context, the article proposes to frame such links as processes of ‘thresholdisation’ and outlines a working definition of DH in literature didactics. The third and last part discusses examples of DH against this background focusing on quantitative analyses of curricula (distant and scalable reading respectively).